Invariants of Multi-Linkoids - Gabrovsek, Bostjan; Güğümcü, Neslihan; Güğümcü, Neslihan (Springer Basel Ag, 2023)
In this paper, we extend the definition of a knotoid to multilinkoids that consist of a finite number of knot and knotoid components. We study invariants of multi-linkoids, such as the Kauffman bracket polynomial, ordered bracket polynomial, the Kauffman skein module, and the T-invariant in relation with generalized T-graphs.
Keywords: Knotoid; multi-linkoid; spatial graph; Kauffman bracket polynomial; Kauffman bracket skein module; theta-curve; theta-graph; Knots; Knotoids